2016
DOI: 10.1021/acs.analchem.6b01635
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Affinity Maturation by Resampling and Microarray Selection

Abstract: Aptamers have significant potential as affinity reagents, but better approaches are critically needed to discover higher affinity nucleic acids to widen the scope for their diagnostic, therapeutic, and proteomic application. Here, we report aptamer affinity maturation, a novel aptamer enhancement technique, which combines bioinformatic resampling of aptamer sequence data and microarray selection to navigate the combinatorial chemistry binding landscape. Aptamer affinity maturation is shown to improve aptamer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In 2016 Kinghorn et al reported a novel strategy of aptamer affinity maturation by library resampling from SELEX sequence data [ 118 ]. This approach relies on the principle that classical SELEX is unlikely to select the best possible aptamer, but is highly likely to select family members of the best possible aptamer.…”
Section: In Silico Aptamer Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016 Kinghorn et al reported a novel strategy of aptamer affinity maturation by library resampling from SELEX sequence data [ 118 ]. This approach relies on the principle that classical SELEX is unlikely to select the best possible aptamer, but is highly likely to select family members of the best possible aptamer.…”
Section: In Silico Aptamer Optimizationmentioning
confidence: 99%
“…While many microarray aptamer optimization processes use mutation and recombination, taking many small evolutionary steps to arrive at an optimum, Resample takes all possible selection sequence information and takes a single evolutionary leap to an optimum. In this way, a single Resample diversification round can be used to hone in on the sequence space containing the best possible aptamer sequence [ 118 ].…”
Section: In Silico Aptamer Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously developed a DNA aptamer against the malaria diagnostic biomarker Plasmodium falciparum lactate dehydrogenase (PfLDH) . We have shown how the aptamer can be used in complex samples, integrated within a 3D printed module to make a portable point‐of‐care device .…”
Section: Introductionmentioning
confidence: 99%
“…Platt et al [7], Knight et al [8], and Rowe et al [9] used microarrays to both evolve aptamers and gain insight into an aptamer binding landscape. Additionally, DNA microarray data has been applied to aptamer specificity landscapes [10], fitness landscape morphology [11], and aptamer affinity maturation [12]. In comparison, the possible sequence space coverage using HTS is much greater, with Illumina's HiSeq HTS capable of yielding sequence data for more than 2 Complexity 70 million sequences from a single lane [13].…”
mentioning
confidence: 99%